CFD Simulation of the effect of increasing the number of impeller blades on the performance of a centrifugal pumps (Journal of Academic Research, 2022)
Centrifugal pumps are used in a wide range of industries, including agriculture and domestic applications. Computational Fluid Dynamics (CFD) is the most widely used simulation and analysis instrument. The flow field characteristics inside the turbomachinery are simulated using a 3-D numerical CFD tool. The flow conditions inside a centrifugal pump can be visualized using CFD simulation. The goal of this paper is to model and simulate the flow of water into a centrifugal pump's impeller. Three impellers were modeled using ANSYS CFX-15 techniques, with the only difference being the number of blades on each one (6, 8, and 10). The operating conditions, such as rotational speed and flow rate, were equal for all three impellers. The impeller's characteristics and results were compared for each in terms of head, efficiency, and cavitation phenomenon. It is found that the head and the efficiency are higher for the case of the impeller with 10 blades than for the two cases of 6 and 8 blades. Furthermore, the beginning of cavitation in the blade passage was detected with an increase in flow rate of more than 14 kg/s, and it was approximately equal for all cases. All the results were consistent with the theory of turbomachinery, demonstrating the effectiveness of CFD simulation tools in the design of this type of equipment